Collecting and managing in situ banana genetic resources information Musa spp. using online resources and citizen science - Jenny, Christophe; Guignon, Valentin; Manyer I Ballester, Felip; Ruas, Max; Rouard, Mathieu (Oxford University Press, 2024)
The Musa Germplasm Information System (MGIS) stands as a pivotal database for managing global banana genetic resources information. In our latest effort, we have expanded MGIS to incorporate in situ observations. We thus incorporated more than 3000 in situ observations from 133 countries primarily sourced from iNaturalist, GBIF, Flickr, Pl@ntNet, Google Street view and expert curation of the literature. This addition provides a more comprehensive and detailed view of banana diversity and its distribution. Additional graphical interfaces, supported by new Drupal modules, were developed, allowing users to compare banana accessions and explore them based on various filters including taxonomy and geographic location. The integrated maps present a unified view, showcasing both in situ observations and the collecting locations of accessions held in germplasm collections. This enhancement not only broadens the scope of MGIS but also promotes a collaborative and open approach in documenting banana diversity, to allow more effective conservation and use of banana germplasm. Furthermore, this work documents a citizen-science approach that could be relevant for other communities.